Strategy Practice and Strategy Process: Family Differences and the Sociological Eye - Whittington, R (2007)
This essay argues for the distinctive position of Strategy-as-Practice research outside the immediate family of Strategy Process. Strategy-as-Practice's fascination with the phenomenon of strategy itself takes it beyond traditional Process perspectives. Relying on the `sociological eye', Strategy-as-Practice treats strategy like any other practice in society, capable of being studied from many different angles. Under the four themes of praxis, practices, practitioners and the profession of strategy as an institutional field, the Essai demonstrates the potential range of research topics, performance notions and methodologies within Strategy-as-Practice. It concludes by proposing five implications of the sociological eye for the conduct of Strategy-as-Practice research, highlighting particularly social connections and relationships, embeddedness, irony, problematized notions of performance and a respect for continuity.